Effects of Hybridization of Carbon and Polypropylene Short Fibers as Reinforcement on Flexural Properties of Fine Aggregate Concretes - Halvaei, Mana; Jamshidi, Masoud; Latifi, Masoud (Civil Engineering Journal, 2016)
Nowadays, the advantages of short fibers as reinforcement in cement based materials are well known. In this paper, the effect of hybridization of short polypropylene (PP) and carbon fibers on flexural properties of a fine aggregate concrete has been investigated. Samples with dimensions of Â containing 2 vol% of the polypropylene and carbon fibers with 6 and 8mm length were made. The PP to carbon fiber proportion in the samples were selected as 100:0, 75:25, 50:50, 25:75 and 0:100. A four-point bending test was carried out on all the samples to investigate the flexural behaviour. It was found that the addition of carbon fibers significantly increases the flexural load (i.e. 260%). The application of PP fibers leads to a 2590% increase in the toughness compared to the control sample. It was also found that the sample with carbon to PP ratio of 75/25 shows the optimum results and it leads to 190% and 2070% increment in the flexural load and toughness, respectively, in comparison to the control sample.